2015
DOI: 10.1080/09658211.2015.1068335
|View full text |Cite
|
Sign up to set email alerts
|

On the adaptive function of children's and adults’ false memories

Abstract: Recent research has shown that memory illusions can successfully prime both children's and adults' performance on complex, insight-based problems (compound remote associates tasks or CRATs). The current research aimed to clarify the locus of these priming effects. Like before, Deese–Roediger–McDermott (DRM) lists were selected to prime subsequent CRATs such that the critical lures were also the solution words to a subset of the CRATs participants attempted to solve. Unique to the present research, recognition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 63 publications
5
25
0
2
Order By: Relevance
“…Jacques et al, 2013), and extracting gist or meaning (Brainerd & Reyna, 1990; Koutstaal, 2006; Schacter, 2001; for recent reviews, see Howe, 2011; Howe et al, 2016; Newman & Lindsay, 2009; Schacter et al, 2011; Schlichting & Preston, 2015). Here we have focused on associative inference, which serves the adaptive function of allowing us to make new connections, and decisions about novel situations, based on flexibly retrieving and recombining information acquired in distinct though related prior experiences (Zeithamova, Schlichting, & Preston, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Jacques et al, 2013), and extracting gist or meaning (Brainerd & Reyna, 1990; Koutstaal, 2006; Schacter, 2001; for recent reviews, see Howe, 2011; Howe et al, 2016; Newman & Lindsay, 2009; Schacter et al, 2011; Schlichting & Preston, 2015). Here we have focused on associative inference, which serves the adaptive function of allowing us to make new connections, and decisions about novel situations, based on flexibly retrieving and recombining information acquired in distinct though related prior experiences (Zeithamova, Schlichting, & Preston, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent research typically showed the priming effect of believed false memories on CRAT problems (Howe, Garner, Charlesworth, & Knott, 2011;Howe, Wilkinson, Garner, & Ball, 2015); and found that the priming effect of false memories was similar to or even stronger than that observed for true memories (Howe, Threadgold, Norbury, Garner, & Ball, 2013;Howe, Wilkinson, Monaghan, Ball, & Garner, 2013). Based on Bernstein et al's work (2015), we predicted that if belief is more influential than recollection when it comes to impacting subsequent behaviors that ostensibly require non-conscious problem-solving processes, no priming effect would be found after beliefs for false memories are withdrawn.…”
Section: The Current Experimentsmentioning
confidence: 99%
“…What this suggests is that the activation level of the falsely remembered words remained high enough to spread through memory during the later problem-solving task. This finding has since been replicated with children (Howe, Garner, Charlesworth, & Knott, 2011) and has recently been extended to recognition tests where, crucially, the locus of these effects have been pin-pointed to activation of the critical lure during the study phase, not the test phase, of the paradigm (Howe, Wilkinson, Garner, & Ball, 2016). That is, priming was equally robust when participants only studied DRM lists or when they studied DRM lists and then received a memory test before solving CRATs.…”
mentioning
confidence: 56%
“…In fact, priming effects are not increased by the presence of memory tests. Specifically, Howe et al (2016) showed that when problem solutions were presented only at test, there was no improvement in solution times or rates. Moreover, when DRM lists were presented only at study, solution times and rates were more robust than in conditions in which DRM lists were studied and tested prior to problem-solving.…”
Section: Discussionmentioning
confidence: 99%